2016
DOI: 10.1016/j.joca.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The anti-NGF antibody muMab 911 both prevents and reverses pain behaviour and subchondral osteoclast numbers in a rat model of osteoarthritis pain

Abstract: SummaryObjectiveNerve growth factor (NGF) has a pivotal role in peripheral hyperalgesia and inflammation; anti-NGF antibodies attenuate pain responses in inflammatory pain models, and in people with osteoarthritis (OA) or low back pain. The aim of this study was to characterise the peripheral mechanisms contributing to the analgesic effects of anti-NGF antibody treatment in an established model of joint pain, which mimics key clinical features of OA.DesignEffects of preventative vs therapeutic treatment with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…The use of osteoprotegerin reduced the development of pain behavior and joint pathology in the MIA model (Sagar et al, 2014 ). As mentioned above, the anti-NGF antibody muMab911 prevented and reversed pain behavior and subchondral osteoclast numbers in the MIA model but did not alter cartilage and synovial pathology (Xu et al, 2016 ).…”
Section: Considerations On Present and Future Therapeutical Possibilimentioning
confidence: 90%
See 1 more Smart Citation
“…The use of osteoprotegerin reduced the development of pain behavior and joint pathology in the MIA model (Sagar et al, 2014 ). As mentioned above, the anti-NGF antibody muMab911 prevented and reversed pain behavior and subchondral osteoclast numbers in the MIA model but did not alter cartilage and synovial pathology (Xu et al, 2016 ).…”
Section: Considerations On Present and Future Therapeutical Possibilimentioning
confidence: 90%
“…Similarly, another study found in the MIA model a late increase of NGF (in conjunction with a neuropathic component), whereas in the first phase, TNF and IL-6 were elevated (Orita et al, 2011a ). The anti-NGF antibody muMab911 prevented and reversed pain behavior and subchondral osteoclast numbers in the MIA model but did not alter cartilage and synovial pathology (Xu et al, 2016 ).…”
Section: Mediators Involved In Oa Painmentioning
confidence: 99%
“…NGF and TrkA are expressed by osteoclasts, and the addition of NGF to monocyte cultures induces the formation of TRAP‐positive multinucleated cells . An anti‐NGF antibody reduced subchondral osteoclast numbers in a rat model of OA pain .…”
Section: Discussionmentioning
confidence: 99%
“…Under inflammatory conditions, NGF expression is up-regulated by cytokines, and inflammatory cells such as mast cells release NGF 2 . Indeed, extracellular NGF levels are higher in inflamed joints and NGF blockade with both TrkA-IgG fusion protein and NGF monoclonal antibodies produces analgesic effects in preclinical settings 3,4 . Relevantly, humanised monoclonal anti-NGF antibodies are effective analgesics in people with osteoarthritis joint pain 5 .…”
Section: Introductionmentioning
confidence: 99%